Acceleration of Organic Vegetables as a Leading Product of Subsidy Housing through Integrated Marketing Communication - Sugeng Hadi Utomo; Santi Merlinda; Ermita Yusida; Vika Annisa Qurrata (Universitas Brawijaya, 2022)
The purpose of the service is to increase the added value of products on organic vegetables in the Perumahan Bulan Terang Utama, Malang City. Organic and superior vegetable products in the Perumahan Bulan Terang Utama include mustard greens, chilies, telang flowers. The activity is based on the concept of integrated marketing communication through 7P (Product, Promotion, Price (Distribution Channel), Place, People (HR), Process, Physical Evidence or Packaging. In this activity, the object of service was assisted in the form of mica, vegetable plastic and product branding stickers, and product logo branding to increase value-added and consumer interest in organic vegetables. In addition, another goal is to increase the branding of organic vegetable production to increase the market share and income of the managers (Botanical Garden community). Through the training and assistance provided, it is hoped that it can increase the productivity of organic vegetables and inspire communities in other regions to care about the environment and the style of healthy living.